Caracterização da criação e avaliação dos impactos do manejo sobre a transferência de imunidade passiva e a sanidade de bezerras leiteiras - Martins, Leoni Ferreira (2019)
The objective was to characterize the rearing of dairy calves and to evaluate the which factors are determinant for passive immunity transfer and health of these animals. Information related to colostrum feeding program, passive immunity transfer, performance, health and reproduction were used, and obtained from a database of 29,583 preweaning heifers belonging to 73 dairy operations. These data were analyzed by frequency distribution for those categorical, and by mean and standard error (SE) for those continue data. A binary logistic regression model was created to verify which management variables could be used to access the passive immunity transfer, at 5 % significance level. Odds ratio (OR) analysis was also performed to evaluate the effects of specific variables on the probability of disease and death occurrence, also at the 5 % significance level. The predominant breed was Holstein with 70.2 % of the animals. From the total calving events, 7.6 % were assisted. The use of fresh colostrum was adopted in 56.6 % of the animals, and 94.2 % of the samples were classified as good quality. The average amount of colostrum ingested was 3.6 liters (SE 0.01), and the efficiency of the colostrum feeding program was 90.4 %. The average daily gain was 760 grams.day-1, and the average body weight at birth was 37.8 kg (SE 0.03). Weight and age of weaning were 102.7 kg (SE 0.14) and 85.1 days (SE 0.11), respectively. The morbidity was 45.8 %, with scours being the most prevalent disease (30.8 %). The average mortality was 6.7 %. embryo transfer calves (OR = 4.56; P < 0.0001), who ingested fresh colostrum (OR = 2.55; P < 0.0001), by bottle (OR = 4.47; P < 0.0001) or esophageal feeder (OR = 3.39; P = 0.01), were more likely to succeed in passive immunity transfer. Passive immunity transfer failure situations increased the odds of scours (OR = 1.21; P = 0.0026) and death (OR = 2.10; P = 0.0001). The odds of respiratory diseases were reduced for animals that ingested equal or more than 10 % of body weight (OR = 0.86; P = 0.0001). Calves that were born from dystocia were more likely to have respiratory disease (OR = 1.54; P = 0.0001) and to die (OR = 1.70; P = 0.0007). In addition, calves diagnosed with both scours and respiratory diseases were more likely to die (OR = 1.28; P = 0.0031). The calf rearing scenario is promising in aspects related to newborn management, colostrum quality, performance and reproductive parameters of heifers. However, there is a need to reduce morbidity and mortality, which are directly affected by delivery type, colostrum feeding program and passive immunity transfer. This, in turn, is associated with the preweaned heifer origin’s service type, the kind of colostrum and the colostrum feeding method adopted.